Measuring spatial accessibility and within-province disparities in accessibility to county hospitals in Shaanxi Province of Western China based on web mapping navigation data - Chi Shen; Zhongliang Zhou; Sha Lai; Li Lu; Wanyue Dong; Min Su; Jian Zhang; Xinyu Wang; Qiwei Deng; Yaru Chen; Xi Chen (BMC, 2020)
Abstract Background The Chinese government proposed the "XIAO BING BU CHU CUN, DA BING BU CHU XIAN" initiative in 2016, which states the rate of health care service provided by county hospitals should reach 90% of overall health care service provision. The prerequisite for achieving this goal is that citizens should be able to access county hospitals' services conveniently and impartially. However, little research has been done on the actual levels of the spatial accessibility of citizens to county hospitals in Western China. Therefore, we aimed to measure the spatial accessibility to county hospitals for county residents and to identify any regional disparities in Shaanxi Province in Western China. Methods We implemented a novel method - involving utilizing navigation data from the AutoNavi web mapping system (knows as Gaode map in Chinese) - to assess the time and distance from villages and neighborhoods to the county hospitals. The navigation data were collected by request through an application-programming-interface using a web crawler (web data extraction tool) in Python. The shortest driving time and distance were extracted from the navigation data. The travel impedance to the nearest provider (TINP) indicator was used to measure spatial accessibility. Results The results show that county residents in Western China's Shaanxi Province have poor spatial accessibility to county hospitals. Only 68.8% of villages and neighborhoods are within 60 min travel time (based on driving mode) to a county hospital, while 13.4% of such villages and neighborhoods are beyond 90 min travel time. Moreover, a significant within-province disparity exists, with residents in the central area enjoying the best accessibility to county hospitals, while the northern and southern areas still need improvements in accessibility. Conclusions Focused health resource planning is required to improve the spatial accessibility to county hospitals and to eliminate regional disparities. Further studies are called for to integrate the navigation data of web mapping systems with GIS methods to the measure spatial accessibility of health facilities in more complex contexts.